An investigation of the Effect of Antihypertensive drugs on Arteriovenous Fistula Maturation in Patients with Hemodialysis - Fatemeh Mahmoudlou; Pouya Tayebi; Aliakbar Moghadamnia; Ali Bijani (Caspian Journal of Internal Medicine)
Background: The maturation of the arteriovenous fistula (AVF) is necessary for successful hemodialysis treatment. However, the role of antihypertensive drugs in influencing AVF maturation remains uncertain. This study investigated the AVF maturation in patients with renal failure treated with antihypertensive medications. Methods: A prospective cohort study was conducted on 73 patients who needed to be treated with hemodialysis through AVF. Demographic information, medication, underlying diseases, blood pressure changes, surgical information, and the time of AVF maturation were collected during the study. Descriptive statistics and survival analysis were employed to assess the outcomes. Results: The mean age of patients was 53.96±13.65 years, with 38 (52.1%) males and 35 (47.9%) females. The mean AVF maturation time was 104.87±1.02 days, and the rate of AVF maturation was 87.7%. Among the comorbidities, the rate of AVF maturation in diabetic patients (78.4%) versus non-diabetic (97.2%) exhibited a notably diminished effect (P = 0.028). There was a significant association between mean intraoperative arterial blood pressure (123.45±2.89 mmHg) and AVF maturation time (P = 0.033). Furthermore, there were not any significant differences in the use of antihypertensive medications on AVF maturation time or rates. Conclusion: Our study findings suggest that the administration of antihypertensive medications did not demonstrate a significant correlation with either the AVF maturation outcome or the time required for maturation.